The end of the Information society. Notes for the Configuration of the new contemporary public space: the society of devisers (2013)
Mass media have often been described as the “new public space” of the current democratic societies (Ortega, 2003: 61). The increased popularity of New Information and Communication Technologies (NICT) is certainly motivating a change in the paradigm: according to the Society of Devisers, it is linked to the notion of collectiveness, it is demystified and fragmented. That is to say, it is taken out of the journalistic showcases and transformed into something alive, incomplete, accessible and multiple. The new society, fissured and emotionally hyperactive, is crossed by the mirror-neurons. This society of anonymous individuals gives public space triggering bursts of energy and enables, in the multidirectional map of devisers, its own central nervous system, although in close connection with the human body. In the next article of revision, the authors describe some of the characteristics which define the advent of that social emergence.